Otak dan Akal dalam Ayat-Ayat Neurosains - Fuad Arif Noor (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
Neuroscience is simply the science that specifically studies Neurons (nerve cells). These nerve cells make up the nervous system, both the central nervous system (brain and spinal cord) and peripheral nerves (31 pairs of spinal nerves and 12 pairs of head nerves). Nerve cells themselves are no longer the smallest unit of nerve cells, the smallest unit of nerve cells (neurons) in synapses, which are the meeting points of two nerve cells that move and forward information (neurotransmitters). At the level of molecular biology, the smallest units are like genes (genetic studies). Generally, neuroscientists focus on nerve cells in the brain. In the Qur'an, the mind has a noble position. It was proven that the word